Depiction of South Kalimantan’s Nature Harmonization in Andaru Folk Stories - Nurbasita Salsabila, Rida; Sariyem, Sariyem; Harpriyanti, Haswinda (Cultural Narratives, 2023)
Andaru folklore depicts the close relationship between society and nature. Nature has a central role in meeting people's living needs, especially rivers and forests in the Meratus Mountains. This research uses literary ecological studies. This research aims to describe the relationship between humans and nature in the South Kalimantan Andaru folklore. Describes how people use nature in the South Kalimantan folklore Andaru. To answer the problem formulation, this research will focus on the interaction between community leaders and nature in the South Kalimantan Andaru folklore and how the people in the South Kalimantan Andaru folklore use nature. The results of this research are that it is known that the Andaru folklore first depicts a close relationship between society and nature. Both realms have a central role in meeting people's living needs. Conclusions based on analysis and discussion, it can be concluded that the relationship between nature and society in Andaru folklore is depicted as very close. The community depends on nature, especially rivers and forests in the Meratus Mountains, as the basis of life and economy.